Theoretical and methodological principles of anti-corruption philosophical and educational concept - Vdovychenko, Eugene (Skhid, 2016)
The article considers the reasons for the spread of corruption in higher education inUkrainefrom analytical and philosophical points of view. Nowadays the higher education ofUkraineis in critical condition. Despite the attempts to make reforms and use the successful experience of other countries we are still lagging behind and may remain in this condition forever. The Ukrainian society is actually in a "legalized falsification" of higher education. This is reflected in the mass, formal legalization for issuing diplomas to persons who graduate from higher education institutions without gaining real competence. The indicators of such falsification in the modern domestic higher education are the facts that desirable marks are put by demand, course papers, bachelor’s and master’s theses are written by request. In the modern Ukrainian country the cult of a diploma of higher education is more important than the real knowledge which makes it possible to develop a professional and general life career the civilized world. Corruption inUkraineis an extremely dangerous and vicious phenomenon which has permeated all the structures and cells of the social organism. It has entrenched in most areas of social life, it is increasing social tension, raising uncertainty about the ability of public authorities to take organizational and practical measures to overcome the systemic crisis. At the international level,Ukrainehas gained the reputation of an extremely corrupt country, which is evidenced by its consistently high ranking in terms of corruption. Corruption in education is generated and distributed primarily by the defects of social relations, the key role in them belonging to the state as an institution of public authorities. That lack of a real democratic and legal state inUkraineleads to systemic causes of the escalation of corruption in the Ukrainian society and spreading this dangerous disease to epidemic proportions. So there is a burning question of whether public authorities and the Ukrainian society are capable to make reforms in the higher education system as the ways and means for this are well known.